Problems attendance in physical education students of technical specialties - Петренко Володимир Іванович, (Vladymyr Petrenko); Петренко Іван Іванович, (Ivan Petrenko) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to examine the relevant aspects of motivation attendance in physical education students of technical specialties and make adjustments to the process of improving the quality of teaching. Material and Methods: during the study used the following methods: general scientific – analysis, comparison, generalization; sociological, questionnaire, interview; Mathematics and statistics. The study involved students of ICT Zhytomyr State Technological University, only 238 people. Results: the tendency changes of success in physical education and physical training of students of ICT. Conclusions: pedagogical experiment confirmed the positive impact of physical education classes in which students choose their maintenance is carried out on a competitive basis in accordance with personal interests and needs.